Carcinogenic and non-carcinogenic risk assessments of arsenic contamination in drinking water of Ardabil city in the Northwest of Iran. Issue 5 (16th April 2018) - Sadeghi, Fatemeh; Nasseri, Simin; Yunesian, Masud; Nabizadeh, Ramin; Mosaferi, Mohammad; Mesdaghinia, Alireza
ABSTRACT: Based on the environmental health assessment framework of the United State Environmental Protection Agency, a quantitative health risk assessment of arsenic in contaminated drinking water in a city in the northwest of Iran has been carried out. In the exposure assessment step, arsenic concentrations in drinking water were determined during four seasons. In addition, the water ingestion rate for different age groups in this region was determined. The concentration of arsenic in 163 collected samples from different locations during four seasons ranged from 0 to 99 μg L −1 . Furthermore, a high percentage of the samples manifested higher levels than the permissible limit of 10 μg L −1 . The total daily water intake rates of four age groups 1 to <2 (group 1), 2 to <6 (group 2), 6 to <16 (group 3), and ≥16 years (group 4) were estimated as 0.86, 1.49, 2.00, and 2.33 L day −1, respectively. Calculating the lifetime average daily dose of arsenic indicated that adults (group 4) had the highest and children (group 1) had the lowest daily intake of arsenic in their entire life. The results of risk characteristic showed that the order of excess lifetime cancer risk via arsenic exposure in the four groups was 4 > 3 > 2 > 1. The estimated risks for all age groups were higher than the acceptable range (1E−6 to 1E−4). The hazard quotient values for all of the classified groups were lower than the recommended limit values (<1), but it cannot be concluded that potential non-carcinogenicity risks are non-existent since the possible exposure to arsenic via food and skin may also pose the risk.